Building Resistance to Stress and Aging - Dienstbier, R. author. aut Link
IX, 380 p.
Keywords: The toughness model proposed in this book incorporates psychological research and neuroscience to explain how a variety of toughening activities - ranging from confronting mental and physical challenges to meditation - sustain our brains and bodies, and ultimately build our mental and psychological capacities degenerated by stress and by aging.